The test meal and exocrine pancreatic function - Brom, Bernard (Division of Human Nutrition, 2017)
The pancreas is a very inaccessible organ situated in the retroperitoneal space. Study of its physiology and function was first confined to animals, where it was possible to construct a pancreatic fistula and thus collect pure pancreatic juice. In addition, pancreatic tissue from animals was also obtainable relatively easily. Early attempts to study the pancreas in man was restricted to patients with pancreatic fistulae, usually the result of surgical procedures. These investigations were on the whole unsatisfactory as the conditions of the experiment were not truly physiological and the juice soon became contaminated and infected. Another method employed later used the intraduodenal tube to collect duodenal contents. The aspirate consisted of a mixture of gastric acid and contents, duodenal juice, bile and succus entericus. Various meals were used to stimulate the pancreatic secretion. Other authors have emphasized the importance of preventing contamination of duodenal contents with gastric juice, and by inserting a second tube or double lumen tube to aspirate the acid from the stomach this was attained. Meal stimulation was now no longer possible so that various drugs and later the two hormones, secretin and pancreozymin, were used to stimulate pancreatic secretion. These two hormones very soon completely replaced any other method of pancreatic simulation. The intravenous injection or infusion of secretin and/or pancreozymin is, however, not a physiological procedure. The initial enthusiasm aroused by this method was tempered due to the varied results obtained by different workers. More recently, Lund has used the test meal to stimulate pancreatic secretion. This technique has been replicated by numerous authors, with promising results reported by all. These reports are characterized by the varied nature of the test meal used, the different position of the intraduodenal tube, the type of suction employed, the period of collection, the length of the test and the type of enzymes estimated. The purpose of the present study is to investigate the physiological responses to the test meal, to define its value in the investigation of pancreatic function and to try and standardise the procedure to obtain optimal pancreatic stimulation.